Learning With The Jigsaw Type Cooperative Method To Improve Student Banking Law and Guarantee Learning Achievement - Nurintan Asyiah Siregar; Nurainun Gulo (International Journal of Science and Environment (IJSE), 2026)
The cooperative learning model is one of the current learning models that is recommended for use in increasing student enthusiasm for learning. The reason for choosing cooperative learning is to improve learning achievement and to improve social relations skills, foster tolerance towards other people’s opinions and be able to think creatively in solving problems and integrating knowledge with skill. This research is classroom action research with the aim to find out whether the Jigsaw cooperative learning model can improve learning achievement for students both individually and in groups. In addition, it also describes the learning activities of students and lecturers during the learning process and student responses to the jigsaw cooperative method. The instruments are tests, observation sheets and questionnaires. The results in cycle 1 showed that only 37,5% of the 40 students scored above 70 on student achievement. In cycle 2 there was an increase in learning achievement, namely 90% of students who scored above 70. Based on these data, the Jigsaw cooperative learning model can improve student achievement.